PILAR PEMBANGUNAN BERKELANJUTAN : KAJIAN PENGELOLAAN SUMBER DAYA ALAM DAN LINGKUNGAN KAMPUNG BATIK REJOMULYO SEMARANG TIMUR - Agus Sarwo Edy Sudrajat (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
The relationship between natural resources and the environment will always be related to sustainable development. In every sustainable development it certainly affects the natural resources and the environment. The impact of sustainable development will lead to economic, social and environmental sectors. However, sustainable development in Indonesia is always identified with high economic growth. It is important to realize that the benchmark for the success of a sustainable development is not only about economic factors. There are still other factors that need to be considered in sustainable development, namely social and ecological. These three factors are better known as three divide sustainable development (Munashinge, 1993). In Indonesia alone it is not enough to depend on only three pillars, it should be applied to five pillars of sustainable development, namely social, economic, ecological, environmental and law enforcement institutions (Surjono, 2010). The purpose of this study is to find out the extent of the role of the five pillars of sustainable development in relation to the management of natural resources and the environment in the Rejomulyo Batik Village. The method used in this study is qualitative, namely assuming that the reality has a plural dimension where truth is dynamic and can be found only through the study of people through their interaction with their social situation (Danim, 2002). This qualitative method emphasizes the study of participants' perspectives through a flexible interactive process, which is intended to understand social conditions from the perspective of participants. Based on the results of the study, it can be concluded that of the five pillars of sustainable development in the management of natural resources and the environment in the village of batik, there are important and fundamental aspects, namely institutions and law enforcement. This aspect is a benchmark for the success of sustainable development in all aspects of resource and environmental management as well as the function of control and evaluation of the three other aspects of economic, social and environmental aspects.